Isolation and Characterization of Kappa-Carrageenan from Hypnea musciformis (Red Alga) Collected from Karachi Coast, Pakistan (Biological Sciences - PJSIR, 2006)
Hypnea musciformis, collected from Karachi coast of Pakistan, was used for the isolation of a thickening and emulsifying agent, carrageenan. Various extraction procedures were employed and the yield of carrageenan obtained was in the range of 34-44%. Total sugar contents were found to be 31.8-55.4%. 3,6-Anhydrogalactose, a component of the total sugar, was present in the range of 19.9-27.6%. Sulphate and ash contents were high, 14.8-41% and 15.4-53%, respectively. The positive rotation of these polysaccharides indicated a predominance of a-D-glycosidic linkages in their structure. IR spectral studies showed kappa-carrageenan as the major phycolloid, with a very small contamination of iota-type carrag- eenan, whereas lambda-type was not detected. Polysaccharides obtained showed a positive elicitor activity in garden peas (Pisum sativum). HPLC analysis indicated the presence of a single major component.